Adsorption of SO2 on ZnO Nanowires Using Activated Carbon by Langmuir Adsorption Isotherm - L. Natrayan; V. Swamy Nadh; Khadijah Mohammedsaleh Katubi; Daoud Ali; Dumesa Gudissa Lemu (Adsorption Science & Technology)
Sulphur dioxide (SO2) is one of the contaminants present in the environment. They are the by-product of combustion, industrial pollution, generation of electricity, etc. After some reactions in the atmosphere, SO2 changes its form and produces acid rain. The presence of SO2 needs to be detected to combat its effect. Many nanosensors are designed to detect the presence of SO2 in the environment. Zinc oxide (ZnO) nanowire sensor is one of those sensors used for SO2 detection. The size, structure, cost-effectiveness, and unique properties made it a choice for sensing purposes. Activated carbon is another compound that has porous substances that helps the adsorbate to settle down on the large surface area of its adsorbent surfaces. Combining the nature of ZnO nanowire and activated carbon, the adsorption of SO2 can be increased. This paper proposes a novel technique involving the activated carbon in the ZnO nanowire sensor to increase its SO2 adsorption capacity and rate. The Langmuir adsorption isotherm is used to find the adsorption efficiency between the solid adsorbent and gaseous adsorbate. MATLAB simulation was carried out for the proposed work in which it is seen that the novel method shows 33.34% efficiency in terms of SO2 adsorption capacity. The response of the proposed sensor shows 23% efficiency over time. The analysis shows that the usage of the activated carbon increases the adsorbent site for SO2 adsorbate to adsorb on the surfaces. According to the adsorption quantity, SO2 level has been obtained in the environment.